2013
DOI: 10.3802/jgo.2013.24.4.342
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence and survival outcome of epithelial ovarian cancer: 30-year national population-based registry in Taiwan

Abstract: ObjectiveTo investigate the changes of incidence and prognosis of epithelial ovarian cancer in thirty years in Taiwan.MethodsThe databases of women with epithelial ovarian cancer during the period from 1979 to 2008 were retrieved from the National Cancer Registration System of Taiwan. The incidence and prognosis of these patients were analyzed.ResultsTotally 9,491 patients were included in the study. The age-adjusted incidences of epithelial ovarian cancer were 1.01, 1.37, 2.37, 3.24, 4.18, and 6.33 per 100,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(131 citation statements)
references
References 44 publications
13
111
5
1
Order By: Relevance
“…The incidence of ovarian cancer increases with age and is most prevalent in the sixth and seventh decades of life with a 5-year survival rate of only 25% [2,3]. Although epithelial ovarian cancer has been managed with surgical resection and chemotherapy, most patients develop a recurrence of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of ovarian cancer increases with age and is most prevalent in the sixth and seventh decades of life with a 5-year survival rate of only 25% [2,3]. Although epithelial ovarian cancer has been managed with surgical resection and chemotherapy, most patients develop a recurrence of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…17 The results of this study were similar to other studies which suggested that patients with mucinous and clear cell type of histopathology had better survival rate than the patients with serous type. 18 The differences between the theoretical results with the results of this study could possibly happen due to lack homogenity of the sample. The sample in this study used all stages of epithelial ovarian cancer.Maybe the results will be more accurate in the same stage, for example, only using samples of stage III.…”
Section: 1011mentioning
confidence: 55%
“…Table IV shows the 5-year observed and relative survival by age group (15-34, 35-44, 45-54, 55-64, 65-74, and 75+) for all the major cancer sites. Relatively higher survival rates were observed in younger patients (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) compared with older patients (65-74, 75+), particularly for sites including the stomach, lung, pancreas, B and CNS, blood (NHL) and cervix. Cancer of the oesophagus, female breast and bladder had higher survival in middle-aged groups (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported on population-based cancer survival in Shanghai (38) and Zhejiang (39); however, these studies primarily focused on a certain or some cancer sites over a short time period. In Taiwan, the survival rates for epithelial ovarian cancer and uterine cancer were reported based upon data from a population-based registry (40,41).…”
Section: Discussionmentioning
confidence: 99%